2022
DOI: 10.34190/ecel.21.1.916
|View full text |Cite
|
Sign up to set email alerts
|

Post- COVID-19 Pandemic Education: The Student Perspective

Abstract: The COVID-19 pandemic can be considered to be a long-term crisis and the outcome of such a crisis is depending on the decisions made during the crisis. As a Higher Education Institution, we are now at a crossroad regarding how to utilize experiences learned during the pandemic. Before the COVID-19 pandemic, there were only a few online study programmes at the Inland Norway University of Applied Sciences, Rena, Norway. During the pandemic, all of the education provided was online.  There are now discussions amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The phenomenon of 'black screens' (cf. Vold et al, 2021) were merely relevant in small parts of the present study, while more meaningful uses of digital tools emerged as important. I found that it seems like when digital tools have a well-defined role in the learning environment, while allowing for some student flexibility, digital forms of communicating and media production tools can have a significantly positive impact on student motivation, on the 'flow' of activities and, and ultimately on the final product.…”
Section: Concluding Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The phenomenon of 'black screens' (cf. Vold et al, 2021) were merely relevant in small parts of the present study, while more meaningful uses of digital tools emerged as important. I found that it seems like when digital tools have a well-defined role in the learning environment, while allowing for some student flexibility, digital forms of communicating and media production tools can have a significantly positive impact on student motivation, on the 'flow' of activities and, and ultimately on the final product.…”
Section: Concluding Discussionmentioning
confidence: 86%
“…The way EiT was organized both during and after the pandemic, seems to have overcome some of the challenges of 'black screens' (cf. Vold et al, 2021) and the concern about making the students passive. Rather, it is more relevant to employ the concept of digital tools or mediating means (cf.…”
Section: Affordances Of Digital Communication Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful delivery of online education is also contingent on educators' motivation and competence with digital platforms. During the pandemic, many teachers reported feeling demotivated by the impersonal nature of digital interactions (Han and Yin, 2016;Vold and Ranglund, 2019;Vold, Lervik, and Holen, 2021). Consequently, the role of educators' motivation in online education delivery warrants further investigation.…”
Section: Teacher's Motivation and Abilities For Online/hybrid Educationmentioning
confidence: 99%